Level of Anxiety with COVID-19 Vaccine Screening Results in Jember Regency - Afandi, Alfid Tri; Putri, Prestasianita; Djuanda, Rosita Oktavia; Rifai, Ahmad (Jurnal Kesehatan Komunitas Indonesia, 2024)
Anxiety can decrease concentration, so it can be dangerous if it happens to someone who is going to do work that could pose a risk of injury. This research aims to identify anxiety levels, identify vaccine screening results COVID-19, and analyze the relationship between anxiety levels and vaccine screening results COVID-19. The independent variable in this study was the level of anxiety, while the dependent variable was the results of vaccine screening for COVID-19. This research had 115 respondents using a sampling technique, namely consecutive sampling. This research design uses a cross-sectional correlation type approach. Use bivariate statistical tests. The results of this study were that most of the vaccine participants' anxiety levels were high, COVID-19 was mild anxiety 54.8%, most respondents had vaccine screening results for COVID-19, namely passing the screening at 92.2%, and there is a relationship between the level of anxiety and the results of the vaccine screening COVID-19 with a value of p=0.000 (p<0.05). It is hoped that this research can provide input and additional information for nursing education regarding people's anxiety levels.